Governance of Intellectual Property Rights in China and Europe - Lee, Nari (Edward Elgar Publishing, Incorporated, 2016)
Intellectual property law performs a number of complex functions in society. To foster innovation and creativity in a society, governments are actively using intellectual property law as a means of governance. Both in China and in Europe, intellectual property law is used to further innovation and cultural policies to increase national competitiveness in a global economy. Due to its impact on global trade, intellectual property laws are increasingly made and influenced by international norms. Against the backdrop of this dynamic global intellectual property norm competition and interaction, this book explores governance of intellectual property rights in China and Europe. This book examines and compares the series of intellectual property law and system reforms in China and Europe. Through the analysis, this book argues that a successful governance of intellectual property rights require not only the adoption of a set of norms but also transformation of the perspectives and the implementing institutions
Description based on publisher supplied metadata and other sources
Keywords: Intellectual property--China; Immaterialgüterrecht; China; Europa